The Gamma Function: basic properties and some applications - Gavilán Gonzales, Maruja (2017)
The goal of the present work is to study some properties and applications of the Gamma Function, denoted by Γ. Initially, we use the Lebesgue Integral Theory in order to prove that the improper integral given by Γ is convergent. We describe the extended domain property of Γ, and we also deduce some elementary properties. We present two different ways of proving that B(x, y) = Γ(x)Γ(y)/Γ(x+y) , where B is the Beta Function. Finally, we include some applications of the Gamma Function, between them some serve up as tools on Reliability Engineering.